2019
DOI: 10.1088/1361-648x/ab32d0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and superconducting properties of Sc5Ir6Sn18

Abstract: Sc5Ir6Sn18 crystallizes with a split variant of the Tb5Rh6Sn18 structure type (space group I41/acd, , ). DFT calculations confirmed the instability of the structural arrangement with the fully occupied and unsplit crystallographic sites. High quality single crystals were grown from a Sn melt. Sc5Ir6Sn18 is a diamagnetic metal showing a superconducting transition at a critical temperature K. The relatively low critical magnetic field 3.2 T as well as the obtained values of the specific heat ratio and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In the whole studied temperature range the same structural model, which is now characterized by reasonable thermal anisotropic displacements and stoichiometric 5:6:18 composition, was refined. The performed refinements confirm Sc 5 Rh 6 Sn 18 to crystallize with Sc 5 Ir 6 Sn 18 structure type 13 . In agreement with this finding, all reflections in the powder XRD patterns of Sc 5 Rh 6 Sn 18 were indexed with the same structural model.…”
Section: Single Crystal and Powder X-ray Diffractionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the whole studied temperature range the same structural model, which is now characterized by reasonable thermal anisotropic displacements and stoichiometric 5:6:18 composition, was refined. The performed refinements confirm Sc 5 Rh 6 Sn 18 to crystallize with Sc 5 Ir 6 Sn 18 structure type 13 . In agreement with this finding, all reflections in the powder XRD patterns of Sc 5 Rh 6 Sn 18 were indexed with the same structural model.…”
Section: Single Crystal and Powder X-ray Diffractionmentioning
confidence: 75%
“…As it is well known, non-centrosymmetric superconductors (SC) are preferable candidates for unconventional superconducting properties, which includes TRS breaking as well. 17 Taking all these observations into account as well as a strong structural disorder reported for isostructural Sc 5 Ir 6 Sn 18 superconductor 13 we performed an extensive study of the crystal structure of Sc 5 Rh 6 Sn 18 applying temperature dependent high-resolution powder and single crystal X-ray diffraction as well as transmission electron microscopy. To understand the obtained structural model the analysis of the chemical bonding situation assuming different structural models is performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24]. The performed diffraction studies showed Sc 5 Rh 6 Sn 18 [space group: I4 1 /acd, a = 13.5529(2) Å, c = 27.0976(7) Å] crystallizes with the Sc 5 Ir 6 Sn 18 type of structure [22]. The structural arrangement can be understood as a corner-sharing trigonal prism array with incorporated cuboctahedra, which are centered by Sc atoms, and 16-vertex polyhedra with the Sn1 atom in the center (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Tm 5 Rh 6 Sn 18 (T c = 2.2 K) is characterized by the coexistence of magnetism and reentrant superconductivity at zero magnetic field [20]. In contrast, conventional BCS superconductivity with an swave gap is observed for Sc 5 Ru 6 Sn 18 (T c = 3.5 K, B c2 = 2.6 T) [21] and Sc 5 Ir 6 Sn 18 (T c = 2.64 K, B c2 = 3.2 T) [22]. Interestingly, recent field-dependent low-temperature thermal conductivity measurements showed nodeless s-wave gaps for both Y 5 Rh 6 Sn 18 and Lu 5 Rh 6 Sn 18 [23].…”
Section: Introductionmentioning
confidence: 99%